2011
DOI: 10.1016/j.devcel.2011.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Repo-Man Coordinates Chromosomal Reorganization with Nuclear Envelope Reassembly during Mitotic Exit

Abstract: SummaryRepo-Man targets protein phosphatase 1 γ (PP1γ) to chromatin at anaphase onset and regulates chromosome structure during mitotic exit. Here, we show that a Repo-Man:PP1 complex forms in anaphase following dephosphorylation of Repo-Man. Upon activation, the complex localizes to chromosomes and causes the dephosphorylation of histone H3 (Thr3, Ser10, and Ser28). In anaphase, Repo-Man has both catalytic and structural functions that are mediated by two separate domains. A C-terminal domain localizes Repo-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
253
3
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(274 citation statements)
references
References 48 publications
11
253
3
7
Order By: Relevance
“…1A), suggesting that the interaction of these two proteins with PP1␥ might be regulated by similar mechanisms. As for the interaction of Repo-MAN with PP1␥, this interaction was shown to be negatively regulated by phosphorylation at Thr-412, a threonine residue that is 17 amino acids downstream of the PP1-binding motif (32) and corresponds to Thr-165 in human Ki67 (Fig. 1A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1A), suggesting that the interaction of these two proteins with PP1␥ might be regulated by similar mechanisms. As for the interaction of Repo-MAN with PP1␥, this interaction was shown to be negatively regulated by phosphorylation at Thr-412, a threonine residue that is 17 amino acids downstream of the PP1-binding motif (32) and corresponds to Thr-165 in human Ki67 (Fig. 1A).…”
Section: Discussionmentioning
confidence: 99%
“…RNAi-The sequences for siRNAs used were as follows: siGL2, 5Ј-CGUACGCGGAAUACUUCGA-3Ј; si31 (Ki67), 5Ј-GGAAGGUCUACAGAGUUCAGGAAUA-3Ј; si32 (Ki67), 5Ј-UCUGGAAGACCUGACUGGCUUUAAA-3Ј; siRepo-MAN, 5Ј-UGACAGACUUGACCAGAAATT-3Ј (32). siRNA transfections were performed using Lipofectamine RNAiMAX (Invitrogen) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The H3T3ph-dephosphorylating enzyme has been shown to be the PP1γ phosphatase specifically targeted to anaphase chromosomes by its regulatory subunit Repo-Man [37,38]. Further studies showed that Repo-Man targeting to chromosomes is negatively regulated through Aurora B phosphorylation explaining the persistent H3T3ph signal observed on telomeres at anaphase [37].…”
Section: Protein Phosphorylation 36mentioning
confidence: 99%
“…In budding yeast, Cdc14 is important and is activated when the cyclin-Cdk1 levels drop below a threshold that allows Cdc14 to be released from a nuclear inhibitor by a pathway that also requires separase (reviewed in Stegmeier and Amon 2004;Rock and Amon 2009). In most other systems, the PP1 and PP2A complexes are most clearly implicated in controlling anaphase and mitotic exit (Kinoshita et al 1990;Vagnarelli et al 2011;Wurzenberger et al 2012).…”
Section: Mitotic Exitmentioning
confidence: 99%
“…PP1 is targeted to a number of structures in anaphase to help to reshape the subcellular architecture during mitotic exit. For example, Repo-Man protein targets PP1 to chromosomes in anaphase to coordinate chromosome decondensation (Vagnarelli et al 2011), and the AKAP149 protein targets PP1 to the nuclear envelope to allow nuclear lamin reassembly (Steen et al 2000). The drop in cyclin -Cdk activity levels in anaphase indirectly reactivates PP2A complexes because Greatwall kinase depends on cyclin -Cdk for its activity.…”
Section: Mitotic Exitmentioning
confidence: 99%